Clinical impact of allergy and pre-medication in CT studies with low-osmolality intravenous iodinated contrast media. Issue 3 (March 2022) - Talmon, A.; Tal, Y.; Moss, J.; Hershkowitz, I.; Shaham, D.; Sosna, J.; Hershko, A.Y.
Abstract : AIM: To evaluate the occurrence and severity of allergic reactions to iodinated contrast media (ICM), including associated risk factors and the impact of pre-medication. MATERIALS AND METHODS: Data on patients who had experienced allergic reactions during outpatient computed tomography (CT) examinations between January 2014 and September 2018 were analysed retrospectively. Response severity was assessed according to validated criteria. A control group was selected among individuals who underwent CT during the study period and did not experience allergic reactions. RESULTS: Screening of 36, 920 CT studies revealed 74 (0.2%) individuals with systemic reactions to ICM. No significant differences in patient characteristics were found among patients who experienced mild ( n= 54), moderate ( n= 17), or severe ( n= 4) reactions. Previous ICM allergy was reported in 10 patients (13.3%). Patients with a history of ICM allergy had mild (9/10) or moderate (1/10) reactions, with one individual showing decreased intensity of the allergic response compared to a previous event. Within the control group, four patients (4%) had previous ICM allergy. In these individuals, lack of allergic reactions could not be attributed to pre-medication. All patients with severe reactions did not have a prior history of ICM allergy. CONCLUSION: Severe allergic reactions to ICM are rare, lack significant risk factors, and do not appear to be impacted by pre-medication. The findings presented herein highlight the need for prospective work that will re-evaluate the yield of pre-medication protocols. Highlights: Risk factors for ICM allergy have a minor effect on the severity of reactions. Severe anaphylaxis is observed in subjects without a prior history of ICM allergy. In subjects with a history of ICM allergy premedication showed little benefit. Anaphylaxis criteria show inaccuracies in the evaluation of reaction severity.